Analisis Pelaksanaan Perlindungan dan Penyelamatan Arsip dari Bencana pada Dinas Perpustakaan dan Kearsipan Kabupaten Blitar Mengacu pada Peraturan Kepala ANRI Nomor 23 Tahun 2015: Studi Kasus pada Kebakaran Sekretariat DPRD Tahun 2025 - Alfina Dwi Rahmatika; Diana Eka Poernamawati (Jurnal Ilmu Sosial dan Humaniora, 2026)
Archives hold important value as a source of information and evidence of organizational governance, so they must be protected from disaster risks, one of which is fire. The fire at the Secretariat of the Blitar Regency Regional House of Representatives caused archival damage and required protection and rescue measures by the Blitar Regency Library and Archives Service. This study analyzes the implementation of archive protection and rescue based on ANRI Head Regulation Number 23 of 2015 and identifies the obstacles encountered. A descriptive qualitative approach was used, with archivists as informants. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman interactive model. Results show that protection and rescue were implemented through the pre-disaster, emergency response, and post-disaster stages, though not yet fully compliant due to limited technical guidelines, facilities, infrastructure, and organizational preparedness. Evacuation, identification, restoration, documentation, and reporting were nevertheless successfully carried out. The study concludes that implementation has generally complied with applicable regulations but still requires improvement in regulatory, preparedness, and infrastructure aspects.